AB1021 2012 update of the french guidelines for the pharmacological treatment of postmenopausal osteoporosis. (23rd January 2014) - Briot, K.; Cortet, B.; Thomas, T.; Guggenbuhl, P.; Roux, C.
Abstract : Objectives: To update the evidence-based position statement published by the French National Authority for Health (HAS) in 2006 regarding the treatment of postmenopausal osteoporosis under the auspices of the French Society for Rheumatology and the GRIO (Groupe de Recherche et d'Information sur les Ostéoporoses), and with the participation of several Societies (Collège National des Gynécologues et Obstétriciens Français, Groupe d'Etude de la Ménopause et du Vieillissement hormonal, Société Française de Chirurgie Orthopédique, Société Française d'Endocrinologie, Société Française de Gériatrie et de Gérontologie). Methods: a panel of multidisciplinary clinician experts in the bone field was enlisted to reach consensus on recommendations. The present manuscript is based on a systematic review and a critical appraisal of the currently available literature according to methodology used by the HAS. Results: – The updated recommendations target women with low trauma fracture defined as severe who require an anti-osteoporotic treatment regardless of the age. In these cases; all the treatments could be considered; zoledronic acid should be used as a first line therapy after hip fracture – In the other situations (absence of fracture and non-severe fracture) the indication of a treatment depends on the BMD and the FRAX® values. All registered treatments can be used, raloxifen and ibandronate use should be limited to women with low peripheral risk fracture – The treatment will be prescribed for a first sequence of 5 years; its continuation or not depends on the 5-year evaluation results. Conclusions: these updated recommendations propose a clarification of the pharmacological management of postmenopausal osteoporosis for all practitioners. Disclosure of Interest: K. Briot Grant/Research support from: Lilly, Consultant for: Amgen, Lilly, MSD, Novartis, B. Cortet Grant/Research support from: Amgen, Lilly, MSD, Novartis, Roche, Consultant for: Amgen, Daiichi-Sankyo, Ferring, GSK, Lilly, MSD, Medtronic, Novartis, Servier, T. Thomas Grant/Research support from: Amgen, Chugaï, Merck, Novartis, Pfizer, Roche, Servier, UCB, Warner-Chilcott, Consultant for: Amgen, Genévrier, GSK, Lilly, Merck, Novartis, Servier, P. Guggenbuhl Grant/Research support from: Lilly, Roche, Consultant for: Amgen, Dai-ichi Sankyo, Lilly, MSD, Novartis, Roche, Servier, C. Roux Grant/Research support from: Bongrain, Amgen, Lilly, MSD, Servier, Consultant for: Amgen, Lilly, MSD, Roche, Novartis, Servier